Policy of Fiscal Federalism in Nepal with References of the Practices of Local Government - Dhakal, Chandra Prasad (International Research Journal of MMC, 2023)
With promulgation of the constitution of Nepal in 2015, Nepal officially adopted a federal form of government as per as legal and constitutional framework. Constitutionally, Nepal follows the three levels of governance ederal, province and local. All levels of governments have certain economic rights to handle the policy and program in their catchment area. This study it analyzes the constitutional provision of fiscal federalism and the special rights of local government interim of financial rights like tax collection, budgeting making and other revenue sharing activities. Qualitative research design has been followed for this study and analyzed the data on the basis of qualitative paradigm, specially, interpretative mode of analysis. Only secondary source of data collected from library and internet study were used in this study. Findings and conclusion of this study have been based on discussions analysis of the legal provision and practice of fiscal federalism. On the basis of discussion, it is found that practice of fiscal federalism did not effectively practice in Nepal. Without proper fiscal federalism, federal government cannot deliver service to local people. The study will help to formulate plan and policy for proper use of financial federalism.